Upaya Menurunkan Nyeri Haid pada Remaja dengan Stimulasi Akupresur pada Titik Akupunktur - Winarni Winarni; Rizqiyyah Rohmatillah; Ikrima Wahyu Shofiyana (PPNI UNIMMAN, 2024)
Dysmenorrhea is experienced by 90% of women in Indonesia, which causes 14% of women not to attend school or do not carry out daily activities, thus reducing their productivity. Adolescent girls are emotionally unstable, if they are not well informed about the menstrual process, they are prone to primary dysmenorrhea. Primary dysmenorrhea is experienced by many adolescents who are in the stage of growth and development, both physical and psychological.Several efforts have been made to reduce pain complaints in cases of Disminorea including non-pharmacological interventions, among others with Rosulullah style treatment, known as Thibbun Nabiwi's treatment, including by listening to Qur'an morrotal and breathing exercises, this treatment is cheap and can be done independently by everyone who experiences. The implementation of socialization at the Aisyiyah Gremet Orphanage is very much needed considering that in the school there are many cases of Dismenorea, and no one has provided an understanding of the case and how to manage it in a non-pharmacological manner so that it can be overcome without giving side effects. It is necessary to hold continuous health education in connection with the lack of an MOU with health institutions, The follow-up plan is to plan health counseling, especially in the health sector, regarding alternative actions that can be taken to overcome menstrual pain in addition to pharmacological drugs..